Ages and petrogenesis of Jurassic and Cretaceous intrusive rocks in the Matsu Islands: Implications for lower crust modification beneath southeastern China. (December 2017) - Chen, Jing-Yuan; Yang, Jin-Hui; Ji, Wei-Qiang
Graphical abstract: Highlights: The 160 Ma granitic magmatism was firstly reported from the Matsu Islands in the coastal area of southeastern China. The Jurassic and Cretaceous granitoids from the Matsu Islands have different Sr-Nd-Hf-O isotopic compositions. Ancient lower crust beneath the coastal area of southeastern China was modified by large-scale mafic magma underplating. Abstract: Major and trace element, whole-rock Sr-, Nd- and Hf-isotope, zircon U-Pb age and Hf-O isotope data are reported for the intrusive rocks from the Matsu Islands in the coastal area of southeastern (SE) China, in order to study the ages, sources and petrogenesis of these rocks and evolution of the lower crust. The rocks include gneissic granite, massive granite, brecciated granite and diabase. Secondary ion mass spectrometer (SIMS) zircon U-Pb dating reveals that the rocks in the Matsu Islands were emplaced at ∼160 Ma, ∼130 Ma and ∼94 Ma. The Jurassic granites (∼160 Ma) have high SiO2 (74.1–74.5 wt%) and K2 O + Na2 O (8.32–8.33 wt%) contents and high Rb/Sr ratios of 0.6–1.2 and (La/Yb)CN ratios of 12.6–19.4. Their relatively high initial 87 Sr/ 86 Sr ratios (0.7074–0.7101), variable and negative εNd (t) values (−9.2 to −5.4), and variable zircon εHf (t) (−17.0 to +5.2) and δ 18 O (4.7–8.1‰) values indicate they were mainly derived from an ancient lower crustal source, but with involvement of high εHf (t) and low δ 18 O materials. The Early Cretaceous diabase (∼130 Ma) has SiO2 content of 56.5 wt%, relatively high MgO concentration, low initial 87 Sr/ 86 Sr ratio and negative εNd (t) value, similar to geochemical features of other Cretaceous mafic rocks in the coastal area of SE China. Zircons from the diabase have high εHf (t) values (−5.5 to +0.2) and relatively low δ 18 O values of 4.2–5.0‰. These characteristics indicate that the parental magma of the diabase was generated by partial melting of enriched lithospheric mantle, which have been metasomatised by altered oceanic crust-derived low-δ 18 O fluids. For the Cretaceous granitoids (∼130 Ma and 94 Ma), they have relatively low SiO2 (68.0–71.3 wt%) and K2 O + Na2 O (5.30–7.55 wt%) contents and low Rb/Sr ratios and (La/Yb)CN ratios of 5.8–7.1. They have low initial 87 Sr/ 86 Sr ratios (0.7071–0.7082), homogeneous εNd (t) (−4.3 to −4.5) and relatively high zircon εHf (t) values (−3.7 to +1.2) and low δ 18 O values (4.6–5.9‰). Their isotopic compositions are similar to those of the diabases in this study as well as other Cretaceous mafic rocks in the coastal area of SE China, suggesting that the sources of the Cretaceous granitoids might be the newly formed lower crust related to the underplated mafic rocks. Whole-rock geochemical, Sr-Nd and zircon Hf-O isotopic compositions indicate that the Jurassic granitoids are most likely generated by partial melting of relatively ancient basement rocks, whereas the Cretaceous granitoids were generated by partial melting of relatively young lower crustal rocks with addition of mantle-derived magma. This distinction implies that the pre-existing ancient lower crust beneath the coastal area of SE China has been modified by large-scale mafic magma underplating. Therefore, underplating of mantle-derived mafic magma would result in modification of the pre-existing ancient lower crust and formation of the relatively juvenile lower crust.